THE DOCUMENTARY LEGACY OF GRAND DUKE MIKHAIL ALEXANDROVICH IN FOREIGN ARCHIVES - Erofeeva G.I. (Вестник Брянского государственного университета)
The article provides an overview of the documentary heritage of Grand Duke Mikhail Alexandrovich. Special attention is paid to foreign archives. The documents reflect the personal life, military service of Grand Duke Mikhail Alexandrovich, his hobbies, leisure, foreign trips, the Orel period, etc. The pages of the biography of Alexei Sergeyevich Matveev, the Grand Duke’s business manager, are also highlighted. In addition, the article contains letters and telegrams from the Grand Duke of Perm, the place of exile of Mikhail Alexandrovich. Previously, these documents were not fully involved. The materials are in a private collection, the archive of the P. Gray family, Great Britain. The personality of the Grand Duke is one of the key figures of a turning point in Russian history. From 1899 to 1904. he was the heir to the throne of the Russian Empire. On March 3, 1917, Nicholas II signed the manifesto of abdication in favor of Grand Duke Mikhail Alexandrovich. Thus, the introduction of materials from foreign archives into scientific circulation will make it possible to supplement the pages of the biography of Grand Duke Mikhail Alexandrovich and help form the funds and exposition of future museums dedicated to the Grand Duke in Perm and the locality of the Bryansk region.